Mother Tongue-Based Education Policy in Nepal: An Ethnic Activists Perspective - Rai, Babu Ram (Journal of TESON, 2026)
The study explored the interpretations of ethnic activists towards policy provisions associated with mother tongue-based education in Nepal. The study has used socio-anthropological approach to policy analysis and adopted an ethnographic design. Information were collected through in-depth interviews with two ethnic activists who have rich experiences advocating for mother tongue-based education. The study shows that ethnic activists have viewed the mother tongue-based education policy as a liberal reform, a historic achievement, and diversification in the education system compared to the past. However, the activists are not fully satisfied, arguing that the policy is imperfect and that the state has distorted the constitutional intent and the activists’ spirit as well. In addition, the study reveals activists’ scepticism that the state has shown malevolent intentions, apathy, and strategic manoeuvring by imposing the burden of establishing and operating separate mother tongue-based schools on linguistic communities. While the state should have made a stronger effort to incorporate multilingual education into ongoing schools. Furthermore, this policy is insufficient to support the fundamental right of every citizen to receive education in their mother tongue, as noted in the Constitution of Nepal. The findings of this study have reflected the idea that the anthropology of policy is a political and ideological tool, and a site of contestation and negotiation.